Dynamic response of turbine blade considering a droplet-wall interaction in wet steam region. (15th February 2023) - Hu, Pengfei; Meng, Qingqiang; Fan, Tiantian; Cao, Lihua; Li, Qi
Abstract: The high-speed impact of liquid droplets on blades in wet steam region seriously affects the safe operation of steam turbine. For blade stability and response characteristics, most studies utilized ideal gas as working medium and few studies focused on the role of droplets in the flow field. In this study, both the distribution information of droplet particles in the flow field and the impact of droplet particles on blades were comprehensively considered. First, the droplet distribution at the last stage inlet was calculated, and then the droplet-wall interaction model was determined and loaded into calculation process. The pressure distribution on blade surface, blade force variation, mechanical properties, and further dynamic response characteristics of blade were analyzed with ideal gas and wet steam models, respectively, by using one-/two-way fluid-structure interaction. Results show that the blade displacement of leading and trailing edges under wet steam model reaches the maximum at near 80% blade height, and there is a low frequency amplitude corresponding to 460 Hz–470 Hz with the peak value in the range of 22Pa–26Pa. The variations of the maximum displacement and maximum equivalent stress of the blade with time are more intense under wet steam model compared with those under ideal gas model. Highlights: The non-uniform incidence of droplets is considered at the inlet of the last stage of the steam turbine. The process of droplet -wall interaction in the last stage is introduced. Two way fluid-structure interaction is applied to study blade response characteristics. The influence of droplet particles on the unsteady characteristics of the flow field in the last stage is studied. The effect of droplet particles on the mechanical properties of the last stage rotor blade is studied.